Evaluating The Level Of Disclosure And Transparency In The Annual Reports Of Companies Listed On The Damascus Securities Exchange - زهرة , شادي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aims to assess the level of disclosure and transparency in the annual reports of the companies listed on the Damascus Securities Exchange during 2019 and issued in 2020. The research was conducted on all companies listed on the Damascus Securities Exchange with the exception of the two telecommunications companies because the annual reports of the two companies were not issued until the end of the eighth month of 2020. This research covers five sectors, namely banking, insurance, industry, agriculture and services. The Standard and Poor’s methodology was used as a tool to measure the level of disclosure and transparency by looking for the availability of 98 features in the annual reports of companies. The research found that the level of disclosure and transparency in the annual reports of companies listed on the Damascus Securities Exchange is low in general, due to the lack of implementation of the legislative framework governing disclosure and transparency instructions on the one hand, and the deficiency of this framework on the other hand.